Building Autonomous Thinking From Practice Using Leading Research - Vásquez, Segundo José Gálvez; Sánchez, Juan de Dios Aguilar; Vásquez, Segundo Rosendo Delgado; Pérez, Uva Peralta; Palomino, Víctor Rafael Loayza; Arce, Jeiden Revilla (Migration Letters, 2024)
The construction of autonomous thinking from practice using leading research, are variables faced by educational institutions to develop critical and creative thinking in the attention to the achievement of learning, deductive attention to the problem started from the general objective: to analyse the construction of autonomous thinking from practice using leading research; it was qualitative approach protagonist, had the teacher as actor-researcher of his own pedagogical practice, in two phases: initial (analytical, reflective, interpretative and critical) and applied (with new pedagogical rationality through nesting of the pre-experimental design pre-test/post-test with a single group, we worked with a population of 135 students in the fourth grade of secondary school in an educational institution in Rioja, the sample was non-probabilistic intentional of 29 students, who provided information to explain the foundations of the teacher’s dominant pedagogical rationality and the contextual factors that conditioned the emergence of the central critical episode, and to construct a new pedagogical rationality (NRP) for the development of written argumentative competence, structured in a psycho-pedagogical programme. In the results the standard deviation of the pre- and post-test scores in writing an argumentative text shows an improvement in the dispersion of the results; in the hypothesis test the calculated Pearson’s correlation coefficient (6.026) is higher than the tabular Pearson’s value (1.7011). Finally it is concluded that the psycho-pedagogical programme based on a NRP significantly developed written argumentative competence.